El PSUC y el eurocomunismo - López Raimundo, Gregorio; Gutiérrez Díaz, Antonio; Campo Vidal, Manuel (Barcelona : Grijalbo, 1981)
Fonds Perrone
Spaans
Monografie
Keywords: eurocommunisme; socialistische partijen; Spanje; Catalonië